‘It’s About Survival’: Court constructions of socio-economic constraints on women offenders in Australian human trafficking for sexual exploitation cases - Baxter, Alexandra; Chazal, Nerida (Anti-Trafficking Review, 2022)
Women make up more than half of the offenders convicted for human trafficking for sexual exploitation in Australia since 2005. This article explores how courts construct the financial motivations for women’s offending to examine how gendered structural constraints are considered in Australian trafficking cases. We explore data from the sentencing remarks and appeal transcripts from the ten cases of women convicted for human trafficking and analyse the two most recent cases to explore how women’s financial considerations are underpinned by the gendered socio-economic pressure of supporting family members. Using data from interviews with Australian judges and anti-trafficking experts, we examine the relationship between structural constraints and women’s agency and the relative weight each of these factors are given in sentencing women trafficking offenders. In doing this, we explore the overlap between victimisation and offending and the tensions between structural constraints and agency, arguing that the former must be taken into consideration when sentencing women trafficking offenders.